Toward mechanistic understanding of wettability alteration in carbonate rocks in the presence of nanoparticles, gelatin biopolymer, and core-shell nanocomposite of Fe3O4@gelatin - Mohammad Ebrahimi; Hossein Ghalenavi; Mahin Schaffie; Mohammad Ranjbar; Abdolhossein Hemmati-Sarapardeh (Scientific Reports)
Abstract Because a significant portion of oil remains in carbonate reservoirs, efficient techniques are essential to increase oil recovery from carbonate reservoirs. Wettability alteration is crucial for enhanced oil recovery (EOR) from oil-wet reservoirs. This study investigates the impact of different substances on the wettability of dolomite and calcite rocks. The substances include silicon dioxide (SiO2) and iron oxide (Fe3O4) nanofluids, gelatin biopolymer, surfactants (sodium dodecyl sulfate (SDS)), Fe3O4/SDS, seawater, and salt solutions (sodium chloride (NaCl) and calcium chloride (CaCl2)). Initially, water-wet rocks were exposed to crude oil for 22 days, resulting in significant contact angle changes. Dolomite and calcite contact angles increased from 56.50° and 50.70° to 107.70° and 104.00°, respectively, due to the presence of heavy and polar elements in the oil. The impact of aging time (7 and 11 days) on rock wettability was studied. Oil-wet rocks were treated with SiO2 and Fe3O4 nanofluids and SDS surfactants for 11 days. The contact angles of the treated rocks decreased significantly. For instance, the contact angles of dolomite and calcite treated with SDS surfactants decreased to 39.07° and 27.38°, respectively, indicating water-wet conditions. Dolomite and calcite surfaces aged with gelatin decreased the contact angles to 38.40° and 34.52°, respectively. Treatment with SiO2 nanofluid reduced the contact angles of dolomite and calcite to 54.27° and 53.17°, respectively, while treatment with Fe3O4 nanofluid decreased the contact angles to 46.08° and 51.16°, respectively. Using Fe3O4/gelatin nanocomposite resulted in contact angles of 26.00° for dolomite and 24.10° for calcite. The wettability alteration mechanism in nanofluids is attributed to structural disjoining pressure. Additionally, NaCl and CaCl2 solutions induced water-wet conditions, known as the salting-out effect, on dolomite and calcite specimens. Consequently, this study demonstrates the potential of various substances, such as nanofluids, surfactants, and salt solutions, to modify rock wettability and improve conditions for enhanced oil recovery.